Anna of Byzantium - Barrett, Tracy (Delacorte Press, 1999)
In the eleventh century the teenage princess Anna Comnena fights for her birthright, the throne to the Byzantine Empire, which she fears will be taken from her by her younger brother John because he is a boy.